A comparative analysis of colour-emotion associations in 16-88-year-old adults from 31 countries - Jonauskaite, Domicele; Epicoco, Déborah; Al-Rasheed, Abdulrahman Saud; Aruta, John Jamir Benzon R; Bogushevskaya, Victoria; Brederoo, Sanne G; Corona, Violeta; Fomins, Sergejs; Gizdic, Alena; Griber, Yulia A.; Havelka, Jelena; Hirnstein, Marco; et al. (My University, 2024)
As people age, they tend to spend more time indoors, and the colours in their surroundings may significantly impact their mood and overall well-being. However, there is a lack of empirical evidence to provide informed guidance on colour choices, irrespective of age group. To work towards informed choices, we investigated whether the associations between colours and emotions observed in younger individuals also apply to older adults. We recruited 7393 participants, aged between 16 and 88 years and coming from 31 countries. Each participant associated 12 colour terms with 20 emotion concepts and rated the intensity of each associated emotion. Different age groups exhibited highly similar patterns of colour-emotion associations (average similarity coefficient of .97), with subtle yet meaningful age-related differences. Adolescents associated the greatest number but the least positively biased emotions with colours. Older participants associated a smaller number but more intense and more positive emotions with all colour terms, displaying a positivity effect. Age also predicted arousal and power biases, varying by colour. Findings suggest parallels in colour-emotion associations between younger and older adults, with subtle but significant age-related variations. Future studies should next assess whether colour-emotion associations reflect what people actually feel when exposed to colour.
Keywords: affect; ageing; colour; cross‐cultural psychology; cross‐modal correspondences; development; perception